TMET-30. ENHANCED RADIOSENSITIZATION OF GLIOMAS BY METABOLIC TARGETING OF SALVAGE PATHWAY OF NAD SYNTHESIS THROUGH NAMPT INHIBITION. (14th November 2022) - Sharma, Pratibha; Xu, Jihong; Huo, Longfei; Ju, Zhenlin; Li, Ziyi; Ban, Kechen; Landesman, Yosef; Sampath, Deepa; Puduvalli, Vinay
Abstract: BACKGROUND: Pathway-specific targeted agents have failed to improve outcome in patients with high grade gliomas. Tumor recurrence is driven by glioma heterogeneity and emergence of therapy-resistant subpopulations. We have previously reported that metabolic targeting of NAMPT, the rate limiting enzyme in the NAD salvage synthesis pathway, circumvents glioma heterogeneity and induces cytotoxicity by mitochondrial membrane depolarization and generation of reactive oxygen species. Based on these data, we examined the potential for NAMPT inhibition to synergize with ionizing radiation to enhance glioma cytotoxicity in vitro and in vivo . METHODS: Using a panel of genetically heterogeneous patient-derived glioma stem-like cells (GSC), we examined the effects of NAD targeting using KPT9274, a potent NAMPT inhibitor, in combination with ionizing radiation on cell proliferation and clonogenicity using Cell Titre Glo assay, colony formation assays and secondary sphere formation. Changes in DNA damage-related proteins were visualized by immunofluorescence assay and confocal microscopy. Effects on gene expression and protein levels were assessed using western blot, reverse phase protein array (RPPA) and RNA Seq. RESULTS: NAMPT inhibition reduced cell proliferation rate, self-renewal and clonogenic capacity in vitro . Combining KPT-9274 with ionizing radiation caused synergistic inhibition of secondary sphere and colony formation of GSC. RPPA and RNASeq results showed downregulation of several DNA repair proteins which was further confirmed using immunofluorescence staining indicating a crucial role for these proteins in glioma resistance to therapies. Results of ongoing in vivo studies to assess the PK/PD, drug toxicity and survival benefits of this combination therapy in orthotopic GSC intracranial glioma mouse model will be reported. CONCLUSIONS: Our results suggest that metabolic targeting through NAMPT inhibition sensitizes glioma cells to radiotherapy. Ongoing studies delineating the mechanistic basis of these effects and their impact in vivo as a potential rationale for clinical assessment will be reported.